A song to my city : Washington, DC - Lancaster, Carol; Farrar, Doug (Georgetown University Press, 2016)
"As a third-generation Washingtonian, Carol Lancaster experienced the city like few others. The first of her family to attend college, she was an undergraduate at Georgetown and earned a PhD at the London School of Economics. After serving in the Department of State in the late 1970s and early 1980s, she returned to the Hilltop to eventually lead the Africa Studies program and then, in 2010, the School of Foreign Service. A friend of presidents and dignitaries all over the globe, an outstanding scholar, and committed to furthering the role of women in international politics, Lancaster put her unique imprint on SFS before passing away from brain cancer in 2014. She spent the last years of her life writing a heartfelt story about her beloved hometown, poignantly and honestly describing the gritty history, politics, environment, society, culture, and larger-than-life local heroes--urban designer Pierre Charles L'Enfant, civic leader 'Boss' Shepherd, and mayor Marion Barry--of the nation's capital. Teeming with informative and amusing anecdotes, as well as beautiful illustrations of landmarks and influential figures, Lancaster's memoir is a deeply personal and passionate paean to the most powerful city in the world"--Provided by publisher